The Supernova Legacy Survey 3-year sample: Type Ia supernovae photometric distances and cosmological constraints - Guy, J; Sullivan, M; Conley, A; Regnault, N; Astier, P; Balland, C; Basa, S; Carlberg, R; Fouchez, D; Hardin, D; Hook, I; Howell, D; et al. (2010)
Aims. We present photometric properties and distance measurements of 252 high redshift Type Ia supernovae (0.15 < z < 1.1) discovered during the first three years of the Supernova Legacy Survey (SNLS). These events were detected and their multi-colour light curves measured using the MegaPrime/MegaCam instrument at the Canada-France-Hawaii Telescope (CFHT), by repeatedly imaging four one-square degree fields in four bands. Follow-up spectroscopy was performed at the VLT, Gemini and Keck telescopes to confirm the nature of the supernovae and to measure their redshifts. Methods. Systematic uncertainties arising from light curve modeling are studied, making use of two techniques to derive the peak magnitude, shape and colour of the supernovae, and taking advantage of a precise calibration of the SNLS fields. Results. A flat ΛCDM cosmological fit to 231 SNLS high redshift type Ia supernovae alone gives ΩM = 0.211 ± 0.034(stat) ± 0.069(sys). The dominant systematic uncertainty comes from uncertainties in the photometric calibration. Systematic uncertainties from light curve fitters come next with a total contribution of ±0.026 on ΩM. No clear evidence is found for a possible evolution of the slope (β) of the colour-luminosity relation with redshift. © 2010 ESO.